Integration of artificial intelligence and liveness detection technologies in the central control system of "Smart home" (MMIT Proceedings, 2025)
This article analyzes the integration of artificial intelligence (AI) and Liveness Detection technologies in the central control systems of smart homes. As smart home systems continue to evolve, the need for enhanced security, adaptability, and accurate user identification is steadily increasing. Liveness Detection strengthens system security by verifying a person’s real presence, while artificial intelligence provides intelligent management and decision-making capabilities. The study examines the process of integrating these two technologies into the central control system of smart homes, outlines their working principles, and evaluates their overall effectiveness in improving system performance and reliability